2018
DOI: 10.5114/pq.2018.75997
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy in Kinsbourne syndrome: a case report

Abstract: Purpose. To evaluate the effect of physiotherapy on ataxia and functional capacity in an individual with Kinsbourne syndrome. Methods. A case study of a 25-year-old male diagnosed with Kinsbourne syndrome undergoing a physiotherapy program in an in-hospital environment for 4 weeks, 5 times a week, with 40-minute sessions. Results. The results in the Scale for the assessment and rating of ataxia (SARA) score decreased significantly after the physiotherapeutic intervention, revealing a significant reduction of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…They found modest evidence that suggested physiotherapy has a positive effect on gait, trunk control, and activity limitations in people with cerebellar dysfunction. Additionally, several clinical trials and a case study conducted on individuals with ataxia have indicated a significant improvement in functional capabilities, such as self-care, gait, and in ataxic symptoms after rehabilitation programs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…They found modest evidence that suggested physiotherapy has a positive effect on gait, trunk control, and activity limitations in people with cerebellar dysfunction. Additionally, several clinical trials and a case study conducted on individuals with ataxia have indicated a significant improvement in functional capabilities, such as self-care, gait, and in ataxic symptoms after rehabilitation programs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%